Effect of Liquid Organic Fertilizer (POC) and NPK Fertilizer Dosage on the Growth and Yield of Cherry Tomato Plants (Solanum Lycopersicum Ver) - Arsy Al Dzismi; Suwanta Suwanta; Achmad Faqih (Asian Journal of Social and Humanities, 2026)
One of the critical factors in increasing agricultural productivity is efficient and environmentally friendly nutrient management. This study aims to determine the effect of the combined dose of liquid organic fertilizer (POC) and NPK fertilizer on the growth and yield of cherry tomato plants (Solanum lycopersicum var. cerasiform). The research was conducted in the Mekarjaya Village research field, Gantang District, Indramayu Regency, West Java, at an altitude of ±36 m above sea level, from June to September 2025. The experiment used a Group Randomized Complete Block (RAK) factorial design with two factors: POC concentration (10, 20, and 30 ml/L) and NPK fertilizer dose (100, 200, and 300 kg/ha), yielding nine treatment combinations, each repeated three times. The observed variables included plant height, stem diameter, number of leaves, root components, number of fruits, fruit weight per plant, fruit weight per plot, and fresh weight of leaves and stems. The data were analyzed using ANOVA, followed by the Scott-Knott test at the 5% level, and Pearson's correlation analysis. The results showed that the combination of POC and NPK fertilizer had a significant effect on most growth parameters and the yield of cherry tomatoes, especially during the medium to late vegetative phase. The best combination was obtained from the treatment of POC 20 ml/L and NPK 200 kg/ha, which produced the highest fruit weight—1.78 kg per plant and 14.27 kg per plot, equivalent to 35.7 tons ha?¹. In addition, plant height and number of leaves at 28–35 HST showed a clear to very strong correlation with fruit weight per plot. Thus, the combination of POC 20 ml/L and NPK 200 kg/ha is recommended to optimally and sustainably increase the growth and yield of cherry tomatoes.